Penyuluhan dan Pemeriksaan Kesehatan sebagai Strategi Menghadapi Masa Transisi Menuju Endemi Covid-19: Education and Health examination as a Strategy for Facing the Transition Period Towards the Covid-19 Endemic - Darmawati, Sri; Putri, Gela Setya Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The COVID-19 pandemic is caused by the coronavirus (Sars-CoV-2). Government programs and policies are gradually establishing controlled environments. In the current situation, the government is preparing several strategies to transition the COVID-19 pandemic to endemic status. Endemic conditions certainly do not mean harmless. It is necessary to educate the community so that the current status of COVID-19 does not carry away the community. To provide health education and routine blood tests (glucose, cholesterol, uric acid) for residents in the Amposari RT 05 RW 03 Kelurahan Kedungmundu, Tembalang District, Semarang, as one of the strategies for preventing and controlling COVID-19 during the transition to endemic. Community service was conducted in Amposari RT 05 RW 03, Kedungmundu Village, Tembalang District, Semarang, in three stages: preparation, implementation, and evaluation. Results: The knowledge of 35 respondents improved, with a mean pre-test score of 41.0, increasing to 78.3 after the post-test. The health examination showed that most residents had normal blood glucose and uric acid levels, but the results for cholesterol were dominated by above normal. Conclusion: Following education, there was a significant increase in knowledge, and most residents had higher cholesterol levels than normal. There was a significant increase in knowledge after education was carried out, and most residents had cholesterol levels above normal.